Instrumentation for the monitoring of toxic pollutants in water resources by means of neural network analysis of absorption and fluorescence spectra - Kuzniz, Tal; Halot, D.; Mignani, Anna Grazia; Ciaccheri, Leonardo; Kalli, Kyriacos; Tur, Moshe; Othonos, Andreas S.; Christofidès, Constantinos; Jackson, David A. (My University, 2007)
The concentration of several pollutants, usually present in industrial waste waters, is predicted by the neural network data processing of absorption and fluorescence measurements in the visible spectral range. Proper network training provides quantitative analysis of many pollutants with sub-ppm resolution. Compact optical fibre instrumentation for absorption spectroscopy and an innovative flowcell for fluorescence measurements enable cost-effective, in situ, nonstop monitoring of waste waters.
Keywords: Pollutants Water; Absorption spectroscopy; Fibre optics; Sensor; Fluorescence spectroscopy; Neural network analysis